Berberis thunbergii Japanese Barberry - Edward Gilman (EDIS, 2007)
This document provides a comprehensive overview of the Japanese barberry (Berberis thunbergii), detailing its characteristics, growth habits, and uses. It describes the plant’s adaptability to various light exposures and soil types, its ornamental features such as persistent red fruits and fall colors, and its potential as a hedge or barrier plant. The document also highlights the plant’s invasive potential and provides information on its hardiness zones, growth rate, and pest resistance. Additionally, it lists several cultivars and discusses common pests and diseases that affect the plant, along with methods for their control. Original publication date October 1999.